2016
DOI: 10.1016/j.jsxm.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Satisfaction and the Importance of Sexual Health to Quality of Life Throughout the Life Course of U.S. Adults

Abstract: Introduction Discussions about sexual health are uncommon in clinical encounters, despite the sexual dysfunction associated with many common health conditions. Understanding of the importance of sexual health and sexual satisfaction among US adults is limited. Aim To provide epidemiologic data on the importance of sexual health for quality of life and people’s satisfaction with their sex lives and to examine how each is associated with demographic and health factors. Methods Data are from a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
187
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(206 citation statements)
references
References 29 publications
7
187
3
9
Order By: Relevance
“…Although sexual functioning is an essential aspect of human life, sexual problems are pervasive, and can result in severe consequences for the individual (and potentially their partner), if not addressed. Sexual dysfunction, defined as difficulty experienced by an individual or a couple during any stage of a normal sexual activity, including physical pleasure, desire, preference, arousal or orgasm [3,4] has been associated with depression and other common mental disorders, relationship discord, poor self-rated health, infertility and overall quality of life [4][5][6][7][8][9][10][11]. Per the published literature, the prevalence of sexual dysfunctions is extremely high, and ranges from 10-63% across various global populations [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although sexual functioning is an essential aspect of human life, sexual problems are pervasive, and can result in severe consequences for the individual (and potentially their partner), if not addressed. Sexual dysfunction, defined as difficulty experienced by an individual or a couple during any stage of a normal sexual activity, including physical pleasure, desire, preference, arousal or orgasm [3,4] has been associated with depression and other common mental disorders, relationship discord, poor self-rated health, infertility and overall quality of life [4][5][6][7][8][9][10][11]. Per the published literature, the prevalence of sexual dysfunctions is extremely high, and ranges from 10-63% across various global populations [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Low sexual satisfaction can relate to poor physical health, whereas sexual satisfaction strongly relates to all domains of quality of life (Flynn et al . ). Users reported that following the intervention, they were more satisfied with physical health, as their increased walking capacity and decreased waist circumference corroborated.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the substantial impact of LUTS on ED, sexual satisfaction, and quality of life among men older than 40 years, the results of the current and previous studies support the importance of a comprehensive assessment of men with LUTS that includes not only the urinary aspect, but also sexual function and sexual satisfaction. 18,19 Conversely, it would be beneficial to assess LUTS in men reporting with sexual dysfunction, as we estimated that a 3-point increase in IPSS score (minimal clinically important difference 33 ) was associated with a decrease of 0.431 points in IIEF-5 score among men with LUTS. This approach would enable a more comprehensive evaluation of 2 highly prevalent and potentially detrimental conditions in men.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although the relationship between LUTS and ED has been well established, 17 data on the interrelationship among LUTS, sexual dysfunction, and sexual satisfaction are limited, particularly in the Brazilian male population and awareness of the importance of sexual satisfaction in general health and quality of life is increasing. More recent studies have shown that overall sexual health was rated as highly important in regard to quality of life, particularly among those who considered themselves to be in good health, 18 and that the presence of comorbidities (ie, hypertension, dyslipidemia, diabetes, and depression) that are known to be associated with sexual dysfunction increases the likelihood of sexual dissatisfaction. 19 As such, the assessment of sexual satisfaction as part of routine clinical practice is gaining attention.…”
Section: Introductionmentioning
confidence: 99%